The structure and content, creativity іntelektualno teacher technology (Pedagogy of Higher and Secondary Education, 2012)
Efimenko S. The structure and content, creativity іntelektualno teacher technology.The article offers the generalized structure of intellectually-creative potential of teacher of technologies. An author characterizes the structural components of this personality formation.
Keywords: intellectual potential; creative potential; intellectually-creative potential of teacher of technologies